Association of Obesity and Negative Acid-Fast Bacilli Finding Among Pulmonary Tuberculosis Patients with Type 2 Diabetes Mellitus - Magfira, Nadya; Mokoagow, Md Ikhsan; Kshanti, Ida Ayu; Helda, Helda (UI Scholars Hub, 2019)
non-diabetes mellitus population. However, it’s effect on PTB in type 2 diabetes mellitus (T2DM) patient is unclear. The study aims to determine the association between obesity and PTB in patient with T2DM. A cross sectional study was held in in-patient, The Department of Internal Medi cine, Fatmawati General Hospital from January 2015 to December 2017. This study includes patient with T2DM who had been diagnosed with PTB and age > 18 years old. In this study negative Acid-fast-bacilli (AFB) founding defined as patient’s sputum is negative by smear microscopy, while obesity define as body mass index > 24.9 kg/m2. From 363 PTB patient with T2DM, 22.59% were obese. Results showed that prevalence of negative AFB founding in PTB patients with T2DM was 81.82% and it was solely associated with obesity (p:0.002, OR=6.36, 95%CI 1.9-21). Obese patients were likely to have negative AFB founding. It suggested that diagnosing PTB in patient with T2DM and obese can’t be solely based on bacteriological confirmation.